Depressive symptoms and physical activity: Post-Confinement Analysis of the Covid-19 Pandemic - Botero-Arboleda, Antonia (2025)
Background: In the face of the Covid-19 pandemic and confinement, people presented mental health problems, affecting mainly young people, who showed depressive symptoms (DS). It is assumed that Physical Activity (PA) may be an associated factor contributing to the reduction of DS. However, the post-confinement analysis between SD and PA still needs to be clarified. Objectives: (1) To study the difference between SDs and PA levels. (2) To compare the SDs according to PA and sex. Methods: Non-experimental quantitative design. A total of 156 young people between 18 and 43 years of age (Mage =22.3; ±5.1) participated. 90 males (Mage = 22.7; ±= 5.0) and 66 females (Mage= 21.6; ±5.2). Depressive symptoms were assessed through the Beck Depression Inventory (BDI). PA was assessed through the International Physical Activity Questionnaire (IPAQ-SF). Results: We found that: (i) there are differences between PA and SD levels; (ii) differences in PA and SD according to sex, and (iii) when the interaction between PA and sex by SD is made, the effects disappear; however, men with Vigorous PA have significantly less SD than women in light and moderate levels. Conclusions: Those with mild PA, independent of sex had higher SDs. Women were more prone to SDs and less active.  These data suggest that PA may be a potential therapeutical and promotional strategy for mental health.